Produtividade de culturas de grãos obtida pela aplicação isolada e combinada de condicionadores de solo - Barboza, Robinson (2015)
The improvement of subsoil chemical quality trough the broadcast lime on soil surface of no-till in Não Me Toque, Rio Grande do Sul State, hasn t been verified. This work was carried out in a farm associated to Cooperativa Agropecuária e Industrial sob Red Oxisol. This work aim to evaluate the efficiency of gypsum and fidagran in single use and mixed in improve chemical soil quality and reduce aluminium toxicity. The work was carried out in long-strips with xx x yy m including the following treatments: a) Check Plot; b) Fidagran; c) Gesso e d) Gesso + Fidagran. The rates of gypsum and fidagran followed the clay content in variable rate. The yields were recorded with a combine equipped with yield sensor. The soybean and maize yields followed the order: check plot, plot<fidagran<gypsum<gypsum+fidagran. In relation to check plot the increases were: fidagran 7 and 21.5%, gypsum 33 and 75.1% and fidagran+gypsum 54 and 125% to soybean and corn, respectively. Therefore, the increase was higher to corn in relation to soybean. Yet, the sum of yield increments when the inputs were applied single were lower than the yield increments when they were mixed.